Meister Eckhart: Pandangan Teologisnya - Eduard Salvatore da Silva; Eddy Kristiyanto (Jurnal Teologi (Journal of Theology), 2020)
Meister Eckhart is a German philosopher, theologian, and mystician of the 13th - 14th century, who has various important perspectives on the philosophical-theological (Human Being-God), spiritual and of course mystical concerning the unity of the soul with God through self-detachment. For Eckhart, Being is identical with God Himself as the only reality. All things outside God are nothingness. This figure was influential in his day, though not free from some excesses of his views that are considered controversial and make his teaching labeled as heresy by the authority of the Church. Nevertheless, his various philosophical-theological, and spiritual insights concerning the concept of Deity, especially in the mystical level, are very relevant to be experienced both in the context of theological studies and the development of spiritual life.